Globalization and the outbreak of COVID-19: An empirical analysis - Mohammad Reza Farzanegan; Mehdi Feizi; Hassan Gholipour Fereidouni (Journal of Risk and Financial Management, 2021)
The purpose of this study is to examine the relationship between the extension of globalization and coronavirus disease 2019 (COVID-19) case fatality rate (CFR) calculated on 28 July 2020 in more than 150 countries. Our regression analyses show that countries with higher levels of socio-economic globalization are exposed to higher levels of CFR. The positive association between the level of globalization of countries and their COVID-19 fatality rate remains robust, controlling for cross-country differences in economic development and demographics, health care costs, health care capacity, quality of governance and continental dummies.
Keywords: 330; COVID-19; case fatality rate; globalization